2014
DOI: 10.1016/j.contraception.2014.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Same-day and delayed reports of pain intensity in second-trimester medical termination of pregnancy: a brief report

Abstract: Adequate, properly timed pain management during second-trimester MTOP is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…[9] Reported need for additional narcotic analgesics for pain control during second-trimester medical abortion has varied from less than 10% to more than 80% in different studies. [1,7,9,10] Oxycodone taken orally at onset of abdominal pain did not reduce maximal pain during medical abortion at less than 11 weeks of pregnancy compared to placebo. [8] Study on intravenous patient-controlled analgesia (IVPCA) with different fentanyl doses compared to morphine showed a fentanyl dose 50ug to be most effective.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…[9] Reported need for additional narcotic analgesics for pain control during second-trimester medical abortion has varied from less than 10% to more than 80% in different studies. [1,7,9,10] Oxycodone taken orally at onset of abdominal pain did not reduce maximal pain during medical abortion at less than 11 weeks of pregnancy compared to placebo. [8] Study on intravenous patient-controlled analgesia (IVPCA) with different fentanyl doses compared to morphine showed a fentanyl dose 50ug to be most effective.…”
Section: Introductionmentioning
confidence: 87%
“…In an earlier study, we reported mean maximal pain VAS of 70 (SD26.5) during second-trimester medical abortion. [7] The study hypothesis was that we can decrease the pain level from VAS 70 to 35 by means of IVPCA. We initially planned to recruit participants in four subgroups of different gestational age and age: late-first-and second-trimester abortions, and teenagers and adult participants separately (ratio 1:2).…”
Section: 1sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…1 This also applies to pain recollection. Previous studies show that both acute [2][3][4][5][6][7][8][9] and chronic pain [10][11][12] might be misremembered. Moreover, the current literature also shows that the way in which pain is remembered influences subsequent pain experiences, [13][14][15] as well as future decisions to engage in activities that may be accompanied by pain.…”
Section: Introductionmentioning
confidence: 99%